Burial and Origin of Permafrost‐Derived Carbon in the Nearshore Zone of the Southern Canadian Beaufort Sea. Issue 3 (3rd February 2020) - Grotheer, H.; Meyer, V.; Riedel, T.; Pfalz, G.; Mathieu, L.; Hefter, J.; Gentz, T.; Lantuit, H.; Mollenhauer, G.; Fritz, M.
Abstract: Detailed organic geochemical and carbon isotopic (δ 13 C and Δ 14 C) analyses are performed on permafrost deposits affected by coastal erosion (Herschel Island, Canadian Beaufort Sea) and adjacent marine sediments (Herschel Basin) to understand the fate of organic carbon in Arctic nearshore environments. We use an end‐member model based on the carbon isotopic composition of bulk organic matter to identify sources of organic carbon. Monte Carlo simulations are applied to quantify the contribution of coastal permafrost erosion to the sedimentary carbon budget. The models suggest that 40% of all carbon released by local coastal permafrost erosion is efficiently trapped and sequestered in the nearshore zone. This highlights the importance of sedimentary traps in environments such as basins, lagoons, troughs, and canyons for the carbon sequestration in previously poorly investigated, nearshore areas. Plain Language Summary: Increasing air and sea surface temperatures at high latitudes leads to accelerated thaw, destabilization, and erosion of perennially frozen soils (i.e., permafrost), which are often rich in organic carbon. Coastal erosion leads to an increased mobilization of organic carbon into the Arctic Ocean, which there can be converted into greenhouse gases and may therefore contribute to further warming. Carbon decomposition can be limited if organic matter is efficiently deposited on the seafloor, buried in marine sediments, and thus removed from the short‐term carbon cycle. Basins, canyons, and troughs near the coastline can serve as sediment traps and potentially accommodate large quantities of organic carbon along the Arctic coast. Here we use biomarkers (source‐specific molecules), stable carbon isotopes, and radiocarbon to identify the sources of organic carbon in the nearshore zone of the southern Canadian Beaufort Sea near Herschel Island. We quantify the contribution of coastal permafrost erosion to the sedimentary carbon budget of the area and estimate that more than a third of all carbon released by local permafrost erosion is efficiently trapped in marine sediments. This highlights the importance of regional sediment traps for carbon sequestration. Key Points: Permafrost organic matter derived from coastal erosion dominates nearshore marine sediments Nearshore basins trapping sediments in the Arctic Ocean efficiently sequester permafrost organic carbon